PREPARATION AND STUDY OF GROWTH STIMULATING ACTIVITY OF 1-PROPYL-4-(3’-AMINO-1’, 2’, 4’-TRIAZOLO-3’- THIOPROPINYL) PIPERIDIN-4-OL - KAZHMUKHANOVICH KISHIBAYEV, Kanagat; SERIKOVICH ASSYLHANOV, Zhanibek; BAZARBEKOVNA MARKINA, Daria; VITALIEVICH NECHIPURENKO, Sergey; AIDAROVNA ATCHABAROVA, Azhar; RISHATOVICH TOKPAYEV, Rustam; ANATOLIEVICH YEFREMOV, Sergey; NIKOLAEVICH KALUGIN, Sergey; LEONIDOVICH RUSSINOV, Vladimir; ORAZOVICH KISHIBAYEV, Kazhmukhan (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Results on the obtaining and the study of a plant growth stimulator based on 1-propyl-4-(3'-amino-1’,2’,4'-triazolo-3'-thiopropinyl) piperidin-4-ol are presented in the article. 1-propylpiperidin-4-on and 3-mercaptopropinyl-5-amin-1,2,4- triazolo were obtained with the basic parameters of the synthesis for synthesizing of 1-propyl-4-(3'-amino-1', 2', 4'-triazolo-3'-thiopropinyl) piperidin-4-ol. The structures of the obtained organic compounds were proved using IR spectroscopy and 1H and 13C NMR spectrometry. The obtained 1-propyl-4-(3’-amino-1’2’4’-triazolo-3’-thiopropynyl)-piperidine-4-ol was tested for growth-stimulating activity on spring wheat grains compared with control (water) and has proved to be a domestic growth regulator «Akpinol-alpha» (KN-2).